Analysis of the Influence of the Value Based Learning and Self Reflection Model of Santri on the Ethical Awareness of Elementary School Students - Muhammad As’ad Humam; Sigit Sugiarto; Imam Ghozali; Muhammad Alfi Syahrin (INNOVASI : JURNAL INOVASI PENDIDIKAN, 2026)
Elementary school students grow within rapidly changing social and digital environments where ethical behavior is not formed automatically but requires intentional educational intervention. Ethical awareness defined as the ability to distinguish right from wrong, consider the consequences of actions, and act according to moral values has therefore become a critical objective of basic education. This study aims to analyze the influence of Value-Based Learning and Santri Self Reflection on the ethical awareness of elementary school students. A quantitative explanatory cross sectional survey design was employed involving 91 students from Grades IV-VI at Daarul Mutqin Elementary School, Bogor, Indonesia. Data were collected using validated and reliable Likert-scale questionnaires and analyzed using multiple linear regression with SPSS. The results indicate that Value-Based Learning has a positive and significant effect on ethical awareness. More importantly, Santri Self Reflection shows a stronger and more dominant influence. Simultaneously, both variables significantly predict ethical awareness with a contribution of 45.5% (R²=0.455), indicating a substantial explanatory power in educational and behavioral research. These findings demonstrate that ethical awareness is most effectively developed through the integration of consistent value habituation and structured self-reflective practices adapted from santri educational traditions. This study contributes to the literature by extending reflective moral learning into elementary education and offers a culturally grounded pedagogical model for strengthening character education in formal schools.